Degradasi (Benzena) Dengan Penambahan Nitrat Dan Bakteri Dari Sedimen Pesisir Karangsong Kabupaten Indramayu - Iklima Hasanah; Yudi Nurul Ihsan; Yeni Mulyani; Indah Riyantini (Jurnal Perikanan Kelautan, 2018)
Until now still found contamination of oil spills due to community activities that perform loading and unloading of ships, one of them in coastal areas Karangsong. The purpose of this research is to get the potential of benzene degradation bacteria derived from coastal sediments of Karangsong and to gain the effect of nitrate addition in the process of benzene reduction. This research uses laboratory experimental method. Concentration of Benzene 0,05 mg/L and variation of nitrate concentration A: 0,2 mg/L, B: 0,3 mg/L, and C: 0,4 mg/L at sea water test medium with interval time observation hour 0, 6, 12, 24, and 48. The results of this study indicate that there is 1 pure gram negative bacteria with the form of bacilli from Karangsong coastal sediment, Indramayu Regency which has the ability to decrease the concentration of benzene C6H6 with the percentage of decrease ranged from 62,66% - 78,41% over 48 hours and a more effective concentration decrease was in treatment C that was 78,41% with the addition of NO3 concentration of 0,4 mg/L.